Políticas de ação afirmativa comparadas no Brasil e na Colômbia - Marcio André de Oliveira dos Santos (Ciências Sociais Unisinos)
The article discusses the political relations between the black movements and the State under the affirmative action policies in two countries, Brazil and Colombia. Both coun-tries have racial formation histories with differences and, at the same time, similarities regarding the set of policies designed to reduce racial inequalities. In this sense, the black movements began to adopt what I call anti-racist racial policies as an instrument of negotiation and struggle with the state apparatus.